2003
DOI: 10.1016/s0378-1097(03)00761-4
|View full text |Cite
|
Sign up to set email alerts
|

Shiga toxins and apoptosis

Abstract: The enteric pathogens Shigella dysenteriae serotype 1 and Shiga toxin-producing Escherichia coli (STEC) cause bloody diarrheal diseases that may progress to life-threatening extraintestinal complications. Although the S. dysenteriae and STEC differ in the expression of a number of virulence determinants, they share the capacity to produce one or more potent cytotoxins, called Shiga toxins (Stxs). Following the ingestion of the organisms, the expression of Stxs is critical for the development of vascular lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 46 publications
2
71
1
2
Order By: Relevance
“…Cell lines such as T84 or HT29 have been in use for decades and may have therefore acquired genetic and epigenetic alterations not found in the primary tumors. Thus, it seems that apoptosis induction by Shiga toxin strongly depends on the cell type, and may rely on different mechanisms (45).…”
Section: Discussionmentioning
confidence: 99%
“…Cell lines such as T84 or HT29 have been in use for decades and may have therefore acquired genetic and epigenetic alterations not found in the primary tumors. Thus, it seems that apoptosis induction by Shiga toxin strongly depends on the cell type, and may rely on different mechanisms (45).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, B subunit causing DNA laddering was lower than A subunit. Similarly in this experiment, studying HeLa cell has suggested that toxin enzymatic activity is necessary to induce apoptosis through a mechanism completely independent of caspase activation (Cherla et al 2003). B subunit of Stx is supposed to be a convenient non-cytotoxic model ) of holotoxin internalization, and Stx A subunit lacks known trafficking motifs (Jackson et al 1999); the A subunit might also modify holotoxin transport via unknown motifs.…”
Section: Discussionmentioning
confidence: 81%
“…In different cell types, toxins may signal apoptosis via different mechanisms (Cherla et al 2003). Therefore, there are highly Stx-sensitive cells with a variant receptor fatty acid, which plays a key role in the kind of intracellular trafficking and sorting of the toxin to the cytosol (O'Loughlin and Robins-Browne 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous recent studies have shown Stx's trigger programmed cell death signaling cascades in intoxicated cells. The mechanisms of apoptosis induced by these toxins are emerging recently, and the data published to date suggest that the toxin may signal apoptosis in different cells types via different mechanisms (Cherla et al, 2003). From what was described above, it is possible to deduce that Shiga toxin may also affect other organs and that apoptotic signs could be considered as toxic cell injuries.…”
Section: Introductionmentioning
confidence: 97%